Pengaruh Konsentrasi Gliserol pada Gelatin Kulit Kelinci terhadap Kadar Air, Ketebalan Film, dan Laju Transmisi Uap Air Edible Film - Qisthi Fadlilah Rahmi; Eka Wulandari; Jajang Gumilar (Jurnal Teknologi Hasil Peternakan, 2022)
Utilization of rabbit skin as a food product has not been carried out optimally, it is not in line with the increasing production of meat. The high protein content makes rabbit skin potential to be used as gelatin. Gelatin is a protein-derived compound that has translucent, colorless, and tasteless properties. This makes gelatin suitable as a raw material for the manufacture of edible films. Edible film is a packaging layer for edible food products. The added glycerol plasticizer can affect the characteristics. This study aims to determine the right concentration to obtain moisture content, film, and water vapor transmission rate of edible film from rabbit skin gelatin. The method used is an experimental method with a completely randomized design (CRD) with 4 treatments consisting of glycerol concentrations of 5%, 10%, 15%, and 20%. Each treatment was repeated 5 times with observed moisture content, thickness, and water vapor transmission rate. The statistical test used ANOVA’s test, then Duncan's advanced test at the 5% level. The results of statistical analysis showed that the different of concentrations glycerol had a significant effect (P<0,05) on the moisture content, thickness, and water vapor transmission rate of edible film. The best film was produced in 10% glycerol (P2) with 8,8% moisture content, 0,15 mm thickness, and 41,9 g/m2.24hours water vapor transmission.